2018
DOI: 10.1021/acschembio.7b01083
|View full text |Cite
|
Sign up to set email alerts
|

Trifunctional High-Throughput Screen Identifies Promising Scaffold To Inhibit Grp94 and Treat Myocilin-Associated Glaucoma

Abstract: Gain-of-function mutations within the olfactomedin (OLF) domain of myocilin result in its toxic intracellular accumulation and hasten the onset of open-angle glaucoma. The absence of myocilin does not cause disease; therefore, strategies aimed at eliminating myocilin could lead to a successful glaucoma treatment. The endoplasmic reticulum Hsp90 paralog Grp94 accelerates OLF aggregation. Knockdown or pharmacological inhibition of Grp94 in cells facilitates clearance of mutant myocilin via a non-proteasomal path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 50 publications
(118 reference statements)
2
40
0
Order By: Relevance
“…are instead sequestered intracellularly (15,30,37,38), specifically within the ER (39), not the cytosol (40). Misfolded myocilin is recognized by the molecular chaperone Grp94 as not competent for secretion, but instead of undergoing efficient degradation, aggregated mutant myocilin accumulates, leading to ER stress, TM cell death (8,15,41), and a cascade that results in early onset ocular hypertension, the causal risk factor for glaucoma.…”
Section: Partially Folded But Stable Molf Domain Variantsmentioning
confidence: 99%
“…are instead sequestered intracellularly (15,30,37,38), specifically within the ER (39), not the cytosol (40). Misfolded myocilin is recognized by the molecular chaperone Grp94 as not competent for secretion, but instead of undergoing efficient degradation, aggregated mutant myocilin accumulates, leading to ER stress, TM cell death (8,15,41), and a cascade that results in early onset ocular hypertension, the causal risk factor for glaucoma.…”
Section: Partially Folded But Stable Molf Domain Variantsmentioning
confidence: 99%
“…It has been reported that the inhibition of Grp94 is an effective approach to the treatment of glaucoma (79,98), supporting the co-aggregation of Grp94 with mutant myocilin and leading to retention within the ER (Fig. 4) (80).…”
Section: Pathogenesis Of Mutant/misfolded Myocilinsmentioning
confidence: 69%
“…However, recent findings (42,78) have suggested that the dominant negative effect may be involved in the pathogenic role of myocilin in glaucoma. Notably, the majority of experimental evidence support gain-of-function as a pathogenic mechanism involved in myocilin mutation-associated glaucoma (21,23,36,37,41,42,67,73,76,79-84).…”
Section: Pathogenesis Of Mutant/misfolded Myocilinsmentioning
confidence: 99%
See 2 more Smart Citations